1999
DOI: 10.1088/0029-5515/39/11/310
|View full text |Cite
|
Sign up to set email alerts
|

Combined heating experiments in ELM-free H modes in JET

Abstract: High power combined NB+ICRF (H)D heating experiments have been carried out in the JET MKIIa divertor configuration, both in deuterium (DD) and in deuterium-tritium (DT) plasmas. Results from a wide range of RF injected power, up to 9.5 MW, NB power up to 22 MW, plasma currents, up to 4.2 MA, and toroidal field values, up to 3.6 T, show a clear improvement in electron temperature, DD reactivity and stored energy with respect to NB only discharges. High energy Neutral Particle Analyser (NPA) data show that accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…For more than 30 years, this method has been used to produce high performance plasmas in a wide range of laboratory fusion devices [1]. The culmination of these studies was the demonstration of efficient ICRF heating of deuterium-tritium plasmas in the TFTR and JET tokamaks in the late 1990s [145][146][147]. More recent studies [148][149][150][151] have confirmed the physics basis for ICRF-based scenarios in a wide range of plasma operational regimes that simulate those anticipated in ITER.…”
Section: Heating and Current Drive Using Ion Cyclotron Waves 451mentioning
confidence: 99%
“…For more than 30 years, this method has been used to produce high performance plasmas in a wide range of laboratory fusion devices [1]. The culmination of these studies was the demonstration of efficient ICRF heating of deuterium-tritium plasmas in the TFTR and JET tokamaks in the late 1990s [145][146][147]. More recent studies [148][149][150][151] have confirmed the physics basis for ICRF-based scenarios in a wide range of plasma operational regimes that simulate those anticipated in ITER.…”
Section: Heating and Current Drive Using Ion Cyclotron Waves 451mentioning
confidence: 99%
“…[1] are included together with their corresponding DD references. In addition, the following DD experiments are included: plasma current scans [25], performance optimization scans with both neutral beam only and combined neutral beam and ICRF [32], power step down experiments [27] …”
Section: Comparisons Of Data With Model Predictionsmentioning
confidence: 99%
“…In the EAST superconducting tokomak [33,34], a longpulse (>15 s) ELM-absent H-mode was achieved recently for the first time with 4.6 GHz LHCD heating and a lithium wall coating. (Here the ELM-absent H-mode is different from the previous ELM-free H-mode, with lower impurity accumulation and core radiation [23][24][25][26].) These ELM-absent H-mode discharges are usually accompanied by an electrostatic edge coherent mode (ECM), as detected by several edge fluctuation diagnostics such as HeBES (helium beam emission spectroscopy), RPL-probe (reciprocating Langmuir probe [35]), GPI (gas puff imaging [36]) and refl.…”
Section: Introductionmentioning
confidence: 98%
“…by resonant magnetic perturbations (RMPs) [6][7][8][9][10], pellet or supersonic molecular beam injection (SMBI) [11][12][13], imposed vertical plasma oscillation [14], lower hybrid current drive (LHCD)-induced 3D edge magnetic topology [15], and impurity seeding [16]; (2) the development of spontaneous stable small/no ELM H-mode scenarios. Significant progress has been made in the past decades, achieving a grassy ELM H-mode in JT-60U [17,18], a type-II ELM H-mode in ASDEX-Upgrade and JET [19][20][21], a mossy ELM H-mode in TCV [22], an ELM-free H-mode in ASDEX-Upgrade, JET, NSTX and DIII-D [23][24][25][26], a quiescent H-mode (QH) in DIII-D [27,28], an enhanced D α H-mode (EDA) in Alcator C-Mod [29,30] and a high-recycling steady H-mode (HRS) in JFT-2M [31,32], and so on.…”
Section: Introductionmentioning
confidence: 99%